2016
DOI: 10.3892/ol.2016.4247
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside and rutin of Nelumbo nucifera induce mitochondrial apoptosis through a caspase-dependent mechanism in HT-29 human colon cancer cells

Abstract: Abstract. The present study demonstrates the mechanism of 2 flavonol glycosides, hyperoside and rutin, in the induction of apoptosis in HT-29 human colon cancer cells through the bioactivity-guided fractionation and isolation method. The chemical structure of hyperoside and rutin, isolated from the roots of Nelumbo nucifera, were established using extensive 1-and 2-dimensional nuclear magnetic resonance experiments and absolute high resolution fast-atom bombardment mass spectrometry, ultraviolet-visible and Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…Hyperoside reduced the impact of H 2 O 2 oxidation in human umbilical vein endothelial cells via ERK signaling where ROS suffered a reduction [38]. Hyperoside reduced intracellular ROS to regulate mitochondrial apoptotic pathways and prevent oxidative damage [39,40]. In our study, hyperoside reduced the intracellular ROS level, which implied that hyperoside may regulate the mitochondrial apoptotic pathway and prevent oxidative damage.…”
Section: Discussionsupporting
confidence: 55%
“…Hyperoside reduced the impact of H 2 O 2 oxidation in human umbilical vein endothelial cells via ERK signaling where ROS suffered a reduction [38]. Hyperoside reduced intracellular ROS to regulate mitochondrial apoptotic pathways and prevent oxidative damage [39,40]. In our study, hyperoside reduced the intracellular ROS level, which implied that hyperoside may regulate the mitochondrial apoptotic pathway and prevent oxidative damage.…”
Section: Discussionsupporting
confidence: 55%
“…Alterations in the expression of Bcl-2 family proteins inhibit dimerization of Bcl-2 family members on the outer mitochondrial membrane, which induces release of mitochondrial proteins, including cytochrome c, Apaf-1, second mitochondria-derived activator of caspase/direct inhibitor of apoptosis-binding protein with low pI and apoptosis-inducing factor, and promotes apoptosis (51,52). Caspase-3 is generally inactive (pro-caspase-3) in cells and activated by death signaling, which catalyzes proteolytic cleavage of PARP as an apoptosis-specific marker (53,54). In the present study, the Bax/Bcl-2 ratio was identified to have increased and PARP was cleaved by caspase-3 via the caspase-9 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The preventive effect on tumor development by LSPCs and flavonoids, extracted from lotus leaves and roots, was exerted through diverse mechanisms including: arrest of the cell‐cycle (Yang et al., ), inhibition of tumor growth (Duan et al., ), proliferation (Chang et al., ; Yang et al., ) and cell migration (Karki, Rhyu, & Kim, ), suppression of MMPs secretion (Ho et al., ; Karki et al., ), and angiogenesis induced by vascular endothelial growth factor (VEGF; Lee et al., ), induction of tumor cell death by apoptosis (Duan et al., ; Guon & Chung ) together with stimulation of antioxidant enzyme activities and immunomodulatory activities (Duan et al., ). Studied cell lines included hepatoma G2 cells (Duan et al., ); breast cancer cell lines: MDA‐MB‐231 cells (Chang et al., ) and MCF‐7 cells (Yang et al., ); skin cancer cells from C57BL/6 J mice (Duan et al., ); colon cancer cell line HT‐29 (Guon & Chung ); and epidermoid cancer cells (A431; Karki et al., ).…”
Section: Health‐promoting Activitiesmentioning
confidence: 99%
“…Moreover, both LL (Ho et al., ) and LR (Karki et al., ) extracts abolished the expression of MMP‐2 and MMP‐9 in a concentration‐dependent manner. Guon and Chung () proposed that que‐3‐gal and que‐3‐O‐rhapyr‐(1→6)‐glupyr, isolated from LR, were responsible for apoptosis induction via the mitochondrial pathway, which was associated with an upregulation of Bax protein and downregulation of Blc‐2 expression. Besides, LSPCs can inhibit tumor growth by 55.3% in terms of average tumor weight (Duan et al., ) and promote cell autophagy at concentrations of 25 to 100 mg/mL (Duan et al., ).…”
Section: Health‐promoting Activitiesmentioning
confidence: 99%